The Arabic Language of Resistance to Polygamy on Social Media: Study on Hastag Ta’addud al-Zaujat - Rika Astari; Abdul Mukhlis; Yusroh Yusroh; Muhammad Irfan Faturrahman (LISANIA: Journal of Arabic Education and Literature, 2023)
The issue of polygamy in Arab society is rarely published in the media. Since the emergence of social media platforms in 2004, such as Instagram, Facebook, and Twitter, the public has communicated and disseminated information freely. On social media, the polygamy controversy is a common subject. The video explanation by Sheikh Doctor Ahmad Karimah Yajib regarding polygamy is one of the videos about the practice that has generated a lot of controversy. This qualitative research relies on primary data from the hashtag Ta’addud al-Zaujat post data (1000 and 5000 posted from 2019 to 2022). The data is disaggregated by expressions in the comments column indicating polygamy resistance. The reasons for resistance to polygamy are not just prompted by Arab netizens' psychological experiences in doing so. However, it is also influenced by the opposition expressed by other internet users from various cultural backgrounds. Expressions of resistance posted in the hashtag Ta’addud al-Zaujat have formed a public opinion to fight against polygamy. This expression of resistance is legitimized by sharing an explanation of the fatwa of Arab Ulama on social media, which only reveals a part of the explanation regarding the polygamy law.